Fatwa-Fatwa Muhammadiyah Seputar Ramadhan dan Titik Beda (Studi Komparatif Muhammadiyah, NU, dan Persis) - Rully Panggabean; Fahril; Mukhtasim Billah (Universitas Garut, 2026)
This article examines Muhammadiyah's fatwas regarding the implementation of Ramadan worship and analyzes their comparative differences with those of Nahdlatul Ulama (NU) and Persatuan Islam (Persis). This research uses a qualitative-descriptive method with a library research approach to official fatwa documents from the Muhammadiyah Tarjih and Tajdid Council, NU's Bahtsul Masail, and Persis's Hisbah Council. The results of the study indicate that the differences in Ramadan fatwas between the three Islamic organizations are primarily due to differences in legal istinbath methodology, particularly in the use of hisab and rukyat, the authority of the madhhab, and the approach to text and context. This article emphasizes that these differences are a form of valid fiqh (jurisprudential) disagreement and are not related to differences in faith, so they need to be addressed moderately and tolerantly in the religious life of Indonesian society.